COMPETITIVIDADE EM ARRANJOS PRODUTIVOS LOCAIS: UM MAPEAMENTO DAS PERCEPÇÕES DAS EMPRESAS DA INDÚSTRIA DE CONFECÇÕES DE MODA ÍNTIMA DE NOVA FRIBURGO, RJ. - Pinto, Hamilton de Souza (2009)
In a global economy, the durable competitive advantages are increasingly supported by elements, as knowledge, motivations and relationships, set in a geographical area or region. The competitiveness is the result of productivity in which companies in a certain locality are able to use the inputs for the production of goods and services valuable. Thus, the aim of this study is to map the perceptions of businesses in cluster of fashion intimate clothing of Nova Friburgo, in order to investigate if this model of industrial organization is competitive. This work expects to contribute to the investigation of the impacts from the concentration of specialized industries in certain localities in business competitiveness